2022
DOI: 10.3844/ajavsp.2022.172.179
|View full text |Cite
|
Sign up to set email alerts
|

Feeding by Logistic Feed (Mash, Silage, Pellet and Wafer) Compared with Conventional Feed on Physiological, Blood Biochemical and Body Weight Gain Recovery in Tropical Sheep Pasca Transportation

Abstract: The process of transportation of animals from one to another area can lead to stress. Animals tend to reduce feed intake which then affects animal performance, so palatable feed is needed, with high energy content, and can speed up the body weight recovery process. This study aimed to evaluate the effect of logistic feed (mash, silage, pellet, and wafer) compared with conventional feed on physiological parameters, blood metabolite profiles, and body weight recovery of tropical sheep pasca transportation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Different forms of feed can affect the rate of fer-Advances in Animal and Veterinary Sciences mentation in the rumen. These results agreed with Retnani et al (2022) who revealed that logistics feed in the form of silage provided feed efficiency and higher income. Yanti et al (2019) added that total mix ration silage derived from agricultural by-products produces fermentation which is well preserved, and this product can be used as ruminant feed.…”
Section: Resultssupporting
confidence: 91%
“…Different forms of feed can affect the rate of fer-Advances in Animal and Veterinary Sciences mentation in the rumen. These results agreed with Retnani et al (2022) who revealed that logistics feed in the form of silage provided feed efficiency and higher income. Yanti et al (2019) added that total mix ration silage derived from agricultural by-products produces fermentation which is well preserved, and this product can be used as ruminant feed.…”
Section: Resultssupporting
confidence: 91%